FinTech Solutions, Financial Inclusion and Sustainable Economic Growth in Developing Countries - Ayeni, Gbenga Joseph Ayeni (African Journal of Stability and Development (AJSD), 2025)
This study examines how innovations in financial technology are changing financial services in developing nations. The study focuses on how FinTech can improve financial inclusion by giving underserved groups access to financial services, thereby fostering sustainable economic growth. Through a qualitative analysis of case studies from Latin America, South Asia, and sub-Saharan Africa, the study investigates how platforms like Paystack, GCash, and M-Pesa have transformed financial access, and how they are encouraging entrepreneurship and raising living standards. However, it draws attention to issues like cybersecurity threats, regulatory gaps, and the digital divide, especially in rural areas. The results emphasise that strong policies, digital literacy initiatives, and infrastructure development are required to take full advantage of FinTech’s potential for inclusive and sustainable growth. Policymakers, financial institutions, and FinTech entrepreneurs can learn from the study how to eliminate barriers to financial inclusion and promote sustainable economic growth in developing countries.